Comparing the effects of two Swedish massage techniques on the vital signs and anxiety of healthy women - Farzaneh Gholami-Motlagh; Mina Jouzi; Bahram Soleymani (Wolters Kluwer Medknow Publications, 2016)
Background: Anxiety is an inseparable part of our lives and a serious threat to health. Therefore, it is necessary to use certain strategies to prevent disorders caused by anxiety and adjust the vital signs of people. Swedish massage is one of the most recognized techniques for reducing anxiety. This study aims to compare the effects of two massage techniques on the vital signs and anxiety of healthy women. Materials and Methods: This quasi-experimental study with a two-group, crossover design was conducted on 20 healthy women who were selected by simple sampling method and were randomly assigned to BNC (Back, Neck, and Chest) or LAF (Leg, Arm, and Face) groups. Massage therapy was carried out for a 14-week period (two 4-week massage therapy sessions and 6 weeks washout stage). Gathered data were analyzed using paired t-test with a significance level of P < 0.05. Results: Both BNC and LAF methods caused a significant decrease in systolic BP in the first stage (P = 0.02, 0.00); however, diastolic BP showed significant decrease only in BNC group (P = 0.01). The mean average of body temperature of LAF group showed a significant decrease in the first stage (P = 0.0.3), and pulse and respiratory rate showed significant decrease in both groups during the second stage (P = 0.00). In addition, anxiety scores showed no significant difference before and after massage therapy (P < 0.05). Conclusions: Massage therapy caused a decrease in systolic BP, pulse, and respiratory rate. It can be concluded that massage therapy was useful for decreasing the vital signs associated with anxiety in healthy women.